Cadet Experience in Learning English for Specific Purposes (ESP) Through Teaching Factory and Micro Internship - Wibowo, Amiruddin Hadi; Oktavia, Wahyuni; Amrullah, Romanda Annas; Onivehu, Adams Ogirima; Muharlisiani, Lusy Tunik (FKIP - Universitas Tanjungpura, 2025)
In the global maritime industry, English proficiency is essential for cadets to perform effectively in international settings. However, English for Specific Purposes (ESP) instruction in maritime education often lacks contextual application. This study explores how the integration of Teaching Factory (TEFA) and micro internships influences cadets